2009
DOI: 10.1016/s1569-1993(09)60005-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic rhinosinusitis in CF

Abstract: Routine CF management often does not include upper airway (UAW) assessment although CFTR defects equally affect the sinonasal mucosa. Up to 50% of CF patients have chronic rhinosinusitis (CRS) and/or nasal polyps, and almost 100% reveal UAW abnormalities on CT scan. CRS impairs quality of life. UAW dysfunction in filtering, humidifying, and warming inspired air affects lower airways and the UAW is a potential site of first colonization and a reservoir for opportunistic bacteria. Therefore, UAW pathology substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 39 publications
0
76
0
7
Order By: Relevance
“…54,55 This was confirmed by Godoy et al 56 who showed a significant association between sinus cultures and lower airway cultures from bronchoalveolar lavage. Genotypes of sinus bacteria were also shown to be concordant with the lower airway, indicating the sinuses also may serve as a reservoir for recurrent lung infection, 57 increasing the importance of maximizing sinus health. There are increased patterns of antimicrobial resistance secondary to multiple antibiotic exposures and increased prevalence of resistant bacteria within the community, particularly S. aureus.…”
Section: Microbiologymentioning
confidence: 99%
“…54,55 This was confirmed by Godoy et al 56 who showed a significant association between sinus cultures and lower airway cultures from bronchoalveolar lavage. Genotypes of sinus bacteria were also shown to be concordant with the lower airway, indicating the sinuses also may serve as a reservoir for recurrent lung infection, 57 increasing the importance of maximizing sinus health. There are increased patterns of antimicrobial resistance secondary to multiple antibiotic exposures and increased prevalence of resistant bacteria within the community, particularly S. aureus.…”
Section: Microbiologymentioning
confidence: 99%
“…Эти ситу-ации с трудом поддаются традиционным методам тера-пии [34]. Ранее указывалось, что полипы образуются к 6-10-летнему возрасту пациента, однако в нашем наблюдении, а также в других зарубежных источниках, можно отметить, что они значительно «помолодели» [35].…”
Section: протеолитический фермент дорназа альфаunclassified
“…Для лечения и профилактики обострений хроническо-го полипозного синусита вводится дополнительная инга-ляция (2 ампулы) через небулайзер [21,22].…”
Section: педиатрическая фармакологияunclassified